2019
DOI: 10.1186/s12913-019-4681-1
|View full text |Cite
|
Sign up to set email alerts
|

Airway clearance services (ACSs) in Australia for adults with chronic lung conditions: scoping review of publicly available web-based information

Abstract: BackgroundConsumers frequently access the internet looking for health information. With the growing burden of chronic disease internationally, strategies are focussing on self-management interventions in community and ambulatory settings. The objective of this scoping review was to describe publicly available information on Australian airway clearance services.MethodsPublicly funded health services network webpages and Google were systematically searched between July and November 2018 using relevant keywords. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, the final number of responses received (121) was very similar to the raw numbers achieved in previous surveys of Australian and New Zealand physiotherapists working with individuals with chronic respiratory conditions [ 15 , 16 ]. Furthermore, a previous study investigating ACTs services for individuals in Australia reported 184 services available, which is similar to the final number of responses received, however it is unable to be determined how many different services are represented in this study [ 31 ]. The survey remained open for 8 months to maximise participation numbers, however, this may have influenced the data collected, as clinical practice may have changed over time.…”
Section: Discussionmentioning
confidence: 74%
“…However, the final number of responses received (121) was very similar to the raw numbers achieved in previous surveys of Australian and New Zealand physiotherapists working with individuals with chronic respiratory conditions [ 15 , 16 ]. Furthermore, a previous study investigating ACTs services for individuals in Australia reported 184 services available, which is similar to the final number of responses received, however it is unable to be determined how many different services are represented in this study [ 31 ]. The survey remained open for 8 months to maximise participation numbers, however, this may have influenced the data collected, as clinical practice may have changed over time.…”
Section: Discussionmentioning
confidence: 74%
“…Using the sampling frame from a systematic scoping review of Australian ACSs ensured that invitations to participate reached existing and potential service providers. 6 The process of obtaining site specific governance approval, and in particular liaising directly with potential participants, was one of the strengths of this study that contributed to the response rate and quality of responses received. The most comparable surveys have response rates of 85% 13 and 72%, 40 however, survey response rates of 70% or higher are considered good and well above the average medical practitioner response rate of less than 30%.…”
Section: Discussionmentioning
confidence: 99%
“…The sample comprised 189 (176 public health services; 13 private providers) potential participants identified by a scoping study conducted by the same authors. 6 Prior to survey dissemination, potentially eligible services were contacted to nominate a single survey respondent (physiotherapist or registered nurse). Services were eligible for inclusion if they currently provided an ACS to adults with chronic lung conditions (asthma, COPD and bronchiectasis) irrespective of setting (outpatient, community or home-based).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway clearance therapies improve secretion clearance, and quality of life [ 5 , 6 ] and reduce the number of acute exacerbations [ 7 ], while exercise therapy improves exercise capacity, quality of life and leads to a longer time to an acute exacerbation [ 8 ]. Up until recently, the most common intervention model for providing the physiotherapy intervention to persons with bronchiectasis was through in-person consultations [ 9 ]. In the global COVID-19 pandemic, the delivery of telehealth has escalated to meet consumer requirements, with physiotherapy services rapidly transitioning to telehealth and frequently with limited preparation or staff training [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%